Isolation, identification and diversity of oleaginous yeasts from Kuching, Sarawak, Malaysia - MICKY VINCENT; HUANG CHAI HUNG; PATRICIA ROWENA MARK BARAN; AFIZUL SAFWAN AZAHARI; DAYANG SALWANI AWANG ADENI (Society for Indonesian Biodiversity, 2018)
Vincent M, Hung MC, Baran PRM, Azahari AS, Adeni DSA. 2018. Isolation, identification and diversity of oleaginous yeasts from Kuching, Sarawak, Malaysia. Biodiversitas 19: 1266-1272. The present study was performed to isolate, identify and determine the diversity of oleaginous yeasts from various sources in Kuching, Sarawak (Malaysia). Microscopic observations via light and scanning electron microscope (SEM) indicated that the yeast isolates were in sizes ranging from 2-3 µm in width and 4-8 µm in length, typical of most unicellular ascomycotic fungi. Polymerase Chain Reaction (PCR) and molecular identification performed on the yeast isolates, targeting the D1/D2 region of the 26S rDNA, identified 6 yeast species from the 21 isolates, namely Pichia manshurica (5/21), Candida krusei (8/21), Candida parapsilosis (1/21), Pichia guilliermondii (2/21), Clavispora lusitaniae (1/21) and Kluyveromyces marxianus (4/21). All 21 yeast isolates accumulated intracellular lipids when grown in nitrogen-limited medium, as tested via Sudan IV staining. The present study is the first to document the production of lipids bodies in C. krusei, C. parapsilosis, and C. lusitaniae. Further investigations to assess the growth kinetics, lipid production efficiencies and lipids profiles of these oleaginous yeasts may provide insights into the possible utilization of these isolates for a variety of scientific, technical and industrial applications.